PEMBERDAYAAN MASYARAKAT TANI KOTA DENPASAR MENUJU PERTANIAN RAMAH LINGKUNGAN MELALUI PELATIHAN PEMBUATAN PUPUK MINERAL PLUS - Indayati Lanya; Subadiyasa N. N.; Tatiek Kusmawati; I G. P.Ratna Adi; N. Dibia; Tati Budi Kusmiyarti; K. Sardiana; N. M. Wikarniti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
Environment issues and go green impacted to perception of political makers both in governmental and privatesector. The organic farming was identical to decrease fertilizer application of chemical fertilizer. This issue shouldbe researched whether chemical fertilizer destroyed environment or vice verse. Since 1998 research found andconcluded that the opposite perception was due to the high dosage organic fertilizer. Dissemination of researchfound that mineral plus processing was conducted in Anggabaya Village. It was done by exercising farmer societywith empowering technology. Raw material of mineral plus fertilizer process has been formulated by the team,and the targets were the farmers and farming family to improve their knowledge in processing fertilizer andapplying it for farmer use. The training was conducted after presentation and discussion so the participant moreunderstood the use of fertilizer and quality of fertilizer. The team as tutors in formulating mineral plus fertilizerand participated by most of participants (90%). The participants were very responsive in mineral plus formulatingand most of them making formulate from the available material. The information from the participant that organicfertilizer yielded low production and farmers use quicklime in papaya garden which produced more sweetened fruits.